2023
DOI: 10.7759/cureus.33784
|View full text |Cite
|
Sign up to set email alerts
|

The Level of School Teachers’ Knowledge About First-Aid Management and Control of Epistaxis in Qassim Region, Saudi Arabia

Abstract: Background: Epistaxis is an acute episode of nasal bleeding commonly caused in children by traumatic injuries in a school setting. It is one of the common ear, nose, and throat emergencies, which should be managed with first-aid measures. To the best of our knowledge, no studies have been conducted among school teachers in the Qassim region of Saudi Arabia regarding this information. This study thus aimed to assess levels of knowledge about first-aid management and control of epistaxis among school teachers in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Alanazy et al found that levels were so low that just 19.4% of participants had good knowledge [ 17 ]. Female gender and prior knowledge of epistaxis management through first aid were significant factors in determining higher levels of awareness [ 17 ].…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Alanazy et al found that levels were so low that just 19.4% of participants had good knowledge [ 17 ]. Female gender and prior knowledge of epistaxis management through first aid were significant factors in determining higher levels of awareness [ 17 ].…”
Section: Reviewmentioning
confidence: 99%
“…Alanazy et al found that levels were so low that just 19.4% of participants had good knowledge [ 17 ]. Female gender and prior knowledge of epistaxis management through first aid were significant factors in determining higher levels of awareness [ 17 ]. Merdad et al found that epistaxis awareness levels among health practitioners at King Abdul-Aziz University Hospital (KAUH) in Jeddah were generally poor.…”
Section: Reviewmentioning
confidence: 99%
“…The misconception of tilting the head backward and applying pressure on the nasal bones may also be common among the public [ 5 ]. Notably, a prospective cross-sectional study conducted among medical practitioners in Kenya revealed a deficiency in knowledge and attitudes toward the first-aid management of epistaxis [ 7 ]. Prior studies in Saudi Arabia have advocated for public education on epistaxis first-aid management through camps and workshops [ 4 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…It can be effectively managed at schools with simple measures such as digital compression on the nose and tilting the head forward. It is important for school teachers to be aware of and knowledgeable about the proper first aid procedures in order to deal with epistaxis promptly and appropriately [ 14 - 16 ]. However, it has been shown that teachers, who are typically the first responders for pediatric epistaxis in schools, have an inadequate or poor understanding of and familiarity with appropriate first aid techniques.…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been shown that teachers, who are typically the first responders for pediatric epistaxis in schools, have an inadequate or poor understanding of and familiarity with appropriate first aid techniques. Evidence suggests that factors such as teachers’ age and educational level, their teaching experience, their previous first aid training, and their exposure to children in need of first aid all affect their first aid knowledge [ 14 ]. In a study conducted in the Qassim region of Saudi Arabia, around 20% of participants had a good level of knowledge regarding the first aid management of epistaxis.…”
Section: Introductionmentioning
confidence: 99%